Physicochemical properties analysis of bamboo salt on chicken emulsion sausage - Sol-Hee Lee; Gye-Woong Kim; Hack-Youn Kim (Journal of Animal Science and Technology, 2020)
Quality characteristics of chicken emulsion sausage manufactured with various levels of NaCl and 9 times heated bamboo salt (0.3%, 0.6%, 0.9%, and 1.2% respectively) were examined. The pH value of chicken emulsion sausage was increase tendency with increasing amount of bamboo salt, on the contrary in case of NaCl sample were decrease tendency with increasing amount of NaCl. Both before and after heating, redness of chicken emulsion sausage with bamboo salt treatments were upward trend with increasing amount of bamboo salt. water holding capacity (WHC) of 1.2% NaCl sample was significantly higher than 0.3%–0.9% (p < 0.05), but 0.9%, 1.2% bamboo salt samples were significantly higher than 0.3, 0.6 % (p < 0.05). Water loss of 1.2% NaCl and 0.9% bamboo salt samples were significantly lower than other treatment (p < 0.05). Protein solubility values significantly increased amount of bamboo salt and NaCl (p < 0.05), and samples of 0.9% NaCl and 0.6% bamboo salt values show similar values. Cooking yield of samples were increased tendency with increasing amount of NaCl and bamboo salt. Also viscosity values of sample containing 1.2% bamboo salt sample showed higher viscosity than other treatments. These results show that containing 1.2% NaCl chicken emulsion sausage and 0.9% bamboo salt chicken emulsion sausage were similar physicochemical properties. Therefore, bamboo salt is suitable for manufacturing chicken emulsion sausage.